Tingkat Kepuasan Pengunjung Apotek Terhadap Pelayanan Kefarmasian di Beberapa Apotek Kabupaten Karanganyar - Novia Amalia; Rolando Rahardjoputro; Adhi Wardhana Amrullah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Health is a pivotal factor in enhancing human quality of life by improving healthcare service quality. Pharmacies serve as crucial healthcare facilities widely frequented by the populace. High-quality pharmaceutical services in pharmacies can gratify patients, foster patient loyalty, and augment patient quality of life. This study aims to ascertain patient satisfaction levels regarding pharmaceutical services at several pharmacies in Karanganyar Regency. This descriptive observational study employed a quantitative approach. Sampling was conducted using non-probability sampling with an accidental sampling technique, resulting in a sample of 105 respondents. Patient satisfaction levels were computed using SPSS Statistics 25. Research findings revealed satisfaction rates for pharmacy service indicators: pharmacy appearance achieved 85.10% (very satisfied), staff friendliness achieved 80.23% (very satisfied), medication information provision achieved 82.66% (very satisfied), medication availability achieved 83.27% (very satisfied), and service speed achieved 87.93% (very satisfied). In conclusion, patients expressed overall satisfaction with pharmaceutical services at several pharmacies in Karanganyar Regency.